Edukacja dzieci socjalizowanych w kulturze ubóstwa jako wyzwanie dla pracy socjalnej (dokument dostępny po zalogowaniu tylko dla osób z dysfunkcją wzroku) - Oliwa-Ciesielska, Monika (Warszawa: Akademia Pedagogiki Specjalnej im. Marii Grzegorzewskiej)
The paper addresses the issues relating to the education and socialization of children living in the culture of poverty, i.e. the situation when the privation affecting the family is not merely a convergence of many incidents, but it becomes a long-lasting experience which results in generational encumbrance.
Keywords: edukacja; dzieci i młodzież; ubóstwo; praca socjalna; Polska; 21 w.